Analisis Kualitas Air pada Sumber Mata Air Di Desa Baumata Kecamatan Taebenu Kabupaten Kupang - Kadang, Luther; Nua, Maria F.; Lulan, Theodore Y. Y. K. (Chemistry Notes, 2022)
Water quality is the nature of water and the content of living this, substances, energy, or other components in water as seen from physical, chemical, and biological characteristics. Pollution of the water environment often occurs, there by reducing water quality. The purpose of this study was to determine the quality and status of contamination of springs based on physical, chemical, and biological parameters in Baumata Village, Taebenu District, Kupang Regency based on the storet method. Determination of the location of water sampling is determined by the purposive sampling technique, while the water sampling refers to the Indonesian National Standard (SNI). Water quality measurements where carried out in situ and ex situ. Parameters tested in situ were temperature, tds, pH, odor and taste, while ex situ were hardness, detergent, and total coliform. The data from the analysis were compared with the quality standars according to Permenkes No. 32 of 2017. The results of the research on spring were reviewed from the parameters of temperature, tds, odor, taste, pH, hardness, and detergent showed that each value was still within safe limits except for parameters total coliform because it exceeds the required quality standars. The status of water contamination in springs based on the STORET method is lightly polluted.